Formation silica gel pad
By designing the storage groove structure and convex transition inclined blocks that are transformed into silicone pads, the problem of uneven stress during the formation of laminated battery cells is solved, and the uniform stress of the battery cells is realized, reducing lithium excretion and warping phenomena , extends the battery life.
Patent Information
- Application Number
- CN202323663401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2033-12-29
AI Technical Summary
During the process of soft-pack lithium-ion batteries, the stacked battery cells have caused lithium extraction and warping problems due to uneven stress. Traditional U-type silicone gaskets are difficult to achieve uniform pressure distribution, resulting in uneven thickness of the battery cells and edge stress. Uneven.
A silicone pad is designed, including a first pad, a second pad and a third pad, forming a receiving groove, and a head, a tail and a side convex body are provided on its sides, which is optimized by transitional oblique blocks and angles. , ensure uniform contact between the head, tail and sides of the battery cell to improve the uniformity of the stress.
Through uniform force distribution, lithium excision and warping of the battery cell during the transformation process is reduced, the overall force uniformity of the battery cell is improved, and the cycle life of the battery is extended.
Smart Images

Figure CN222190837U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of lithium batteries, and in particular to a formed silica gel pad. Background Art
[0002] In the production process of soft-pack lithium-ion batteries, the formation process is crucial to the formation of battery performance. This process can activate the activity inside the battery and form a layer of SEI film, thereby ensuring that the battery has excellent charge and discharge performance and cycle life, while also ensuring the integrity of the battery appearance.
[0003] At present, in order to improve production efficiency, the industry generally uses automated hot-pressing fixture formation machines to perform formation operations under heating and pressure conditions. This method greatly shortens the production time of batteries. In this hot-pressing formation process, special pressure fixtures and auxiliary materials are required to ensure that the battery cells are firmly fixed while being subjected to uniform pressure.
[0004] The traditional method is to use a U-shaped silicone gasket with solid material on both sides as a support pad for the battery cell. This gasket is located above and below the battery cell and is placed between the clamps of the fixture together with the battery cell. The main function of the silicone gasket is to protect the battery cell and prevent its surface from being indented when it is under pressure.
[0005] Laminated cells are a type of soft-pack lithium battery, and the lamination technology is considered to be an effective way to increase the energy density of lithium-ion batteries. However, there are still many defects:
[0006] 1. The zebra coating technology in the previous process is difficult to achieve "zero thinning" at the edge, resulting in a thinner thickness at the head of the corresponding stacked battery cell, insufficient force during the formation process, and severe lithium deposition during the later cycle process;
[0007] 2. Compared with conventional wound cells, laminated cells have no surrounding force constraints. During the formation process, the stress in the middle of the cell is greater than that on the surrounding areas, resulting in uneven stress around the edges during the formation process, which leads to lithium deposition in the cell;
[0008] 3. The single-sided sheets at the head and tail of the stacked battery cell are coated with a single layer. When subjected to stress, the stress on the two sides is inconsistent, which can easily cause the single-sided sheet to warp, and further lead to lithium deposition at the head and tail. Utility Model Content
[0009] In view of the deficiencies in the prior art, the utility model provides a chemically formed silica gel pad.
[0010] The utility model discloses a chemically formed silica gel pad, comprising: a first pad body, a second pad body and a third pad body, wherein two ends of the second pad body are respectively connected to the first pad body and the third pad body, and the first pad body and the third pad body are arranged opposite to each other, and the first pad body, the second pad body and the third pad body form a receiving groove; one of the first pad body and the third pad body is provided with a first convex body on the side facing the receiving groove, and the first convex body is distributed at the edge of the side surface.
[0011] According to one embodiment of the utility model, the first convex body includes a head convex strip, a tail convex strip and two side convex strips, the head convex strip and the tail convex strip are arranged opposite to each other, the two ends of one side convex strip are respectively connected to one end of the head convex strip and the tail convex strip, and the two ends of the other side convex strip are respectively connected to the other end of the head convex strip and the tail convex strip.
[0012] According to one embodiment of the utility model, it also includes a first transition oblique block, a second transition oblique block and two third transition oblique blocks, the first transition oblique block connects the head ridge and the side, the second transition oblique block connects the tail ridge and the side, and the two third transition oblique blocks respectively connect the two side ridges and the side.
[0013] According to an implementation manner of the present utility model, a first angle α is formed between the first inclined surface of the first transition inclined block and the side surface, and the value of the first angle α is: 22.636°≤α≤22.928°.
[0014] According to one embodiment of the present invention, the height of the head convex strip is H 1 , the height of the first transition ramp is H 2 , the width of the first transition ramp is D 1 , where H 1 =H 2 =2.1±0.015mm, D 1 =3mm-6mm.
[0015] According to an embodiment of the present invention, a second angle β is formed between the second inclined surface of the second transition oblique block and the two third transition oblique blocks and the side surface, and the value of the second angle β is: 21.653°≤β≤21.949°.
[0016] According to one embodiment of the present invention, the height of the tail ridge and the two side ridges is H 3 The height of the second transition inclined block and the third transition inclined block is H 4 , the width of the second transition inclined block and the third transition inclined block is D 2 , where H 3 =H 4 =2.0±0.015mm, D 2 =3mm-6mm.
[0017] According to one embodiment of the present invention, the hardness of the formed silicone pad is 40HA-80HA.
[0018] According to an embodiment of the present invention, the material of the chemically formed silicone pad is silicone-based silicone.
[0019] According to an embodiment of the present invention, the other of the first cushion body and the third cushion body is provided with a second protrusion on the side facing the receiving groove, and the second protrusion is the same as the first protrusion.
[0020] The beneficial effect of the utility model lies in that by arranging the first convex body in the accommodating groove, when the stacked battery cell is placed in the accommodating groove, the head, tail and sides of the stacked battery cell are in contact with the first convex body, thereby achieving thickening of the head, tail and sides of the stacked battery cell. When the clamp is clamped, the force on the entire stacked battery cell will be more uniform, thereby solving the problems of lithium deposition and warping of the stacked battery cell due to uneven force during the formation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0022] Figure 1 is a side cross-sectional view of the formed silica gel pad;
[0023] Figure 2 is a front view of the first cushion body;
[0024] Figure 3 is another front view of the first pad body;
[0025] Figure 4 is another side cross-sectional view of the formed silica gel pad;
[0026] Figure 5 It is another side cross-sectional view of the formed silica gel pad.
[0027] Description of Reference Numerals
[0028] 1- first cushion body;
[0029] 2- second cushion body;
[0030] 3- the third cushion body;
[0031] 4-accommodating tank;
[0032] 5-first convex body; 51-head convex strip; 52-tail convex strip; 53-side convex strip;
[0033] 6-first transition inclined block; 61-first inclined surface;
[0034] 7- second transition inclined block;
[0035] 8- the third transition oblique block;
[0036] 9-Second slope;
[0037] 10-side;
[0038] 20-Stacked battery cells. DETAILED DESCRIPTION
[0039] The following will disclose multiple embodiments of the present invention with drawings. For the purpose of clear description, many practical details will be described together in the following description. However, it should be understood that these practical details should not be used to limit the present invention. In other words, in some embodiments of the present invention, these practical details are not necessary. In addition, in order to simplify the drawings, some conventional structures and components will be depicted in a simple schematic manner in the drawings.
[0040] In addition, in the present utility model, the descriptions of "first", "second", etc. are only used for descriptive purposes, and do not specifically refer to the order or sequence, nor are they used to limit the present utility model. They are only used to distinguish components or operations described with the same technical terms, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present utility model.
[0041] like Figure 1-Figure 5 As shown, Figure 1 is a side sectional view 10 of the formed silica gel pad; Figure 2 is a front view of the first pad body 1; Figure 3 is another front view of the first pad body 1; Figure 4 is a cross-sectional view of another side 10 of the formed silica gel pad; Figure 5 It is another side sectional view 10 of the formation silica gel pad. The formation silica gel pad of the present application comprises a first pad body 1, a second pad body 2 and a third pad body 3, one end of the first pad body 1 is connected to one end of the second pad body 2, one end of the third pad body 3 is connected to the other end of the second pad body 2, the first pad body 1, the second pad body 2 and the third pad body 3 are connected to form a receiving groove 4, and the laminated battery cell 20 is located in the receiving groove 4. In this embodiment, the cross section of the receiving groove 4 is U-shaped, and after the laminated battery cell 20 is placed, the first pad body 1 and the second pad body 2 are in contact with the surface of the laminated battery cell 20 on one side facing the receiving groove 4.
[0042] In specific application, the first pad 1 is provided with a first protrusion 5 on a side surface 10 facing the receiving groove 4 (i.e., one of the side walls of the receiving groove 4). The first protrusion 5 is distributed along the edge of the side surface 10. At the same time, the first protrusion 5 is also in contact with the laminated battery cell 20. The first protrusion 5 includes a head protrusion 51, a tail protrusion 52, and two side protrusions 53, all of which are located on the side surface 10 of the first protrusion 5. One end of one side protrusion 53 is connected to one end of the head protrusion 51, and the other end thereof is connected to one end of the tail protrusion 52; one end of the other side protrusion 53 is connected to the other end of the head protrusion 51, and the other end thereof is connected to the other end of the tail protrusion 52. The four are connected to form a rectangle. When in use, after the laminated battery cell 20 is placed, the head protrusion 51, the tail protrusion 52, and the two side protrusions 53 are connected to each other. The side ridges 53 are in contact with the four sides of the laminated battery cell 20 respectively, so as to improve the tightness of the connection between the sides of the laminated battery cell 20 and the first pad body 1. It can also be understood that the distance between the sides of the laminated battery cell 20 and the first pad body 1 is reduced by setting the head ridge 51, the tail ridge 52 and the two side ridges 53. When the clamp clamps the silicone pad, the force on the sides of the laminated battery cell 20 can be increased, so that the force of the entire laminated battery cell 20 tends to be uniform, avoiding the occurrence of lithium precipitation.
[0043] Furthermore, the chemically formed silica gel pad also includes a first transition bevel 6, a second transition bevel 7 and two third transition bevels 8 arranged on the side 10 of the first pad body 1, the first transition bevel 6 connects the head convex strip 51 and the side 10, the second transition bevel 7 connects the tail convex strip 52 and the side 10, and the two third transition bevels 8 correspond to the two side convex strips 53, respectively, and connect the side convex strips 53 and the side 10. Specifically, the first transition bevel 6 has a first bevel 61, and there is a first angle α between the first bevel 61 and the side 10, wherein the value range of the first angle α should satisfy 22.636°≤α≤22.928°; similarly, the second transition bevel 7 and the two third transition bevels 8 both have a second bevel 9, and there is a second angle β between the second bevel 9 and the side 10, wherein the value range of the second angle β should satisfy 21.653°≤β≤21.949°. In addition, in this embodiment, the maximum height of the head convex strip 51 protruding from the side surface 10 is set to H. 1 The maximum height of the first transition inclined block 6 protruding from the side surface 10 is H 2 , where H 1 =H 2 =2.1±0.015mm; Similarly, the maximum height of the tail ridge 52 and the two side ridges 53 protruding from the side surface 10 is H 3 The maximum height of the second transition inclined block 7 and the two third transition inclined blocks 8 protruding from the side surface 10 is H 4 , where H 3 =H 4=2.0±0.015mm; In this embodiment, the width of the first transition ramp 6 on the side 10 is set to D 1 The width of the second transition bevel 7 and the two third transition bevels 8 on the side 10 is D 2 , where D 1 =D 2 =3mm-6mm, preferably, D 1 =D 2 =5mm. By setting the height, width and inclination angle of the head convex strip 51, the tail convex strip 52, the side convex strip 53, the first transition bevel block 6, the second transition bevel block 7 and the third transition bevel block 8, on the one hand, the corresponding formation silicone pad can be adapted according to the actual specifications of the laminated battery cell 20, and on the other hand, the damage of the laminated battery cell 20 during the formation stage due to the excessive angle corresponding to the formation silicone pad can be avoided.
[0044] It should also be noted that the above is only an explanation of the structure of the first pad body 1. In another embodiment, the third pad body 3 can adopt the same structure as the first pad body 1, that is, the side 10 of the third pad body 3 facing the accommodating groove 4 is provided with a second protrusion, wherein the specific structure of the second protrusion is the same as that of the first protrusion 5, which will not be repeated here. See above for details.
[0045] Specifically, in order to prevent the entire material of the formed silicone pad from being too hard and thus causing damage to the laminated battery core 20 , the material of the formed silicone pad in this embodiment is silicone-based silicone, and the hardness of the formed silicone pad should meet 40HA-80HA.
[0046] For further verification, a conventional silicone pad is used as a comparative example. The conventional silicone pad does not have the structure of the first convex body 5 and the second convex body, and its surface is a flat surface. At the same time, the first angle α and the second angle β of different angles are used as embodiments for verification. The verification results are shown in Table 1, which shows the test data of the comparative example and the embodiment.
[0047] Table 1
[0048] The first angle α The second angle β Lithium precipitation Example 1 22.636° 21.653° Slight lithium deposition Example 2 22.782° 21.801° Basically no lithium precipitation Example 3 22.928° 21.949° Slight lithium deposition Comparative Example 0 0 Severe lithium deposition
[0049] Through experimental verification, it can be seen that when the first convex body 5 and the second convex body are not added in the comparative example, there is a serious lithium deposition situation; when the first angle α and the second angle β adopt extreme values, a slight lithium deposition phenomenon will occur; when the first angle α and the second angle β adopt the middle average value, there is basically no lithium deposition phenomenon, which greatly improves the problem of lithium deposition.
[0050] To summarize, by arranging the first convex body 5 in the accommodating groove 4, when the stacked battery cell 20 is placed in the accommodating groove 4, the head, tail and sides of the stacked battery cell 20 are in contact with the first convex body 5, thereby achieving the thickening of the head, tail and sides of the stacked battery cell 20. When the clamp is clamped, the force on the entire stacked battery cell 20 will be more uniform, thereby solving the lithium deposition and warping problems of the stacked battery cell 20 due to uneven force during the formation process.
[0051] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of the claims of the present invention.
Claims
1. A chemically formed silica gel pad, It is characterized in that include: A first pad body (1), a second pad body (2) and a third pad body (3), wherein two ends of the second pad body (2) are respectively connected to the first pad body (1) and the third pad body (3), and the first pad body (1) and the third pad body (3) are arranged opposite to each other, and the first pad body (1), the second pad body (2) and the third pad body (3) constitute a receiving groove (4); one of the first pad body (1) and the third pad body (3) is provided with a first protrusion (5) on a side surface (10) facing the receiving groove (4), and the first protrusion (5) is distributed at the edge of the side surface (10).
2. The chemically formed silica gel pad according to claim 1, It is characterized in that The first convex body (5) comprises a head convex strip (51), a tail convex strip (52) and two side convex strips (53); the head convex strip (51) and the tail convex strip (52) are arranged opposite to each other; two ends of one side convex strip (53) are respectively connected to one end of the head convex strip (51) and one end of the tail convex strip (52); and two ends of the other side convex strip (53) are respectively connected to the other end of the head convex strip (51) and the other end of the tail convex strip (52).
3. The chemically formed silica gel pad according to claim 2, It is characterized in that It also includes a first transition oblique block (6), a second transition oblique block (7) and two third transition oblique blocks (8), wherein the first transition oblique block (6) connects the head convex strip (51) and the side surface (10), the second transition oblique block (7) connects the tail convex strip (52) and the side surface (10), and the two third transition oblique blocks (8) respectively connect the two side convex strips (53) and the side surface (10).
4. The chemically formed silica gel pad according to claim 3, It is characterized in that A first angle α is formed between the first inclined surface (61) of the first transition inclined block (6) and the side surface (10), and the value of the first angle α is: 22.636°≤α≤22.928°.
5. The chemically formed silica gel pad according to claim 3, It is characterized in that The height of the head convex strip (51) is H 1 , the height of the first transition inclined block (6) is H 2 , the width of the first transition ramp (6) is D 1 , where H 1 =H 2 =2.1±0.015mm, D 1 =3mm-6mm.
6. The chemically formed silica gel pad according to claim 4, It is characterized in that A second angle β is formed between the second inclined surface (9) of the second transition inclined block (7) and the two third transition inclined blocks (8) and the side surface (10), and the value of the second angle β is: 21.653°≤β≤21.949°.
7. The chemically formed silica gel pad according to claim 5, It is characterized in that The height of the tail ridge (52) and the two side ridges (53) is H. 3 , the height of the second transition inclined block (7) and the third transition inclined block (8) is H 4 The width of the second transition bevel block (7) and the third transition bevel block (8) is D 2 , where H 3 =H 4 =2.0±0.015mm, D 2 =3mm-6mm.
8. The chemically formed silica gel pad according to claim 1, It is characterized in that The hardness of the chemically formed silica gel pad is 40HA-80HA.
9. The chemically formed silica gel pad according to claim 1, It is characterized in that The material of the chemically formed silica gel pad is silicone-oxygen silica gel.
10. The chemically formed silica gel pad according to any one of claims 1 to 9, It is characterized in that The other of the first pad body (1) and the third pad body (3) is provided with a second protrusion (5) on the side surface (10) facing the receiving groove (4), and the second protrusion (5) is the same as the first protrusion (5).
